Simplify 12a-(4b+4a)-b

12a-4b-4a-b
=> 8a-5b

8a - 5b

Step-by-step explanation:

12a-(4b+4a)-b

= 12a - 4b - 4a - b

Combine like terms

= 8a - 5b

Related Questions

Use substitution to solve the system.

3x-2y = 17

x = 3y+15

3x - 2y = 17
substitute x with 3y+15

3(3y+15) - 2y = 17
use the distributive property

9y + 45 - 2y = 17
combine like terms 9y and -2y

7y + 45 = 17
subtract 45 from both sides

7y = -28
divide both sides 7 to isolate the variable, y.

y = -4

To solve for x:

x = 3y + 15
plug in -4 for y

x = 3(-4) + 15
multiply

x = -12 + 15

x = 3

Evaluate the following expression. NEED THE ANSWER ASAP!!!!!!!!!!!! (-6)-2

-36
-1/36
1/36
36

C. 1/36

Step-by-step explanation:

Simplify (2a^3) (5a^4)

Step-by-step explanation: Think of this problem of having two parts. The coefficients 2 and 5 and the powers and . To multiply these two terms together, simply multiply their coefficients and we have to add the exponents because we are multiplying powers.

2 × 5 = 10

× =

With this, you multiply the coefficients first, (2)(5)=10
Then when you multiply the variables, you add the exponents,

So you would end up with:

Why are reliability and validity important for assessment? How are content validity and criterion-related validity used to establish construct validity? Support your position.